Solar Neutrons and Related Phenomena - Dorman, Lev.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
This book presents the first comprehensive compilation and review of the extensive body of experimental and theoretical material on solar neutrons and related phenomena published in the scientific literature over the last sixty years. Phenomena related to solar neutrons are more specifically: the decay products of solar neutrons solar gamma rays generated in processes like nuclear reactions between solar energetic charged particles and matter of the solar atmosphere, as well as by the capture of solar neutrons by hydrogen atoms in the solar atmosphere the propagation of solar neutrons, solar gamma rays and other secondary particles through the solar photosphere, chromosphere and corona, as well as through interplanetary space and through the Earth's atmosphere. Models and simulations of particle acceleration, interactions, and propagation processes show that observations of solar neutrons and gamma rays in space and in the Earth's atmosphere yield essential and unique information on the source function of energetic solar particles, as well as on the chemical composition and density distribution of plasma in the solar atmosphere. The results described in the book may also be useful for astrophysical studies of other stars and different astrophysical objects, as well as for space weather problems. The book will serve as a reference work for researchers and students in solar physics, plasma, neutron, and gamma ray physics, as well as in cosmic ray physics, space science, geophysics and those researching space weather problems.
Interactions of Charged, Accelerated Particles in the Solar Atmosphere, and the Generation of Secondary Energetic Particles and Radiation: Pioneer Results -- The Events of August 1972 and the Discovery of Solar Gamma-Radiation -- The Events of June 1980 and June 1982, and the Discovery of Solar Neutrons -- Space Probe Observations of Solar Neutron and Gamma Ray Events -- Solar Neutron Propagation in the Earth$1 (Bs Atmosphere, and the Sensitivity of Neutron Monitors and Other Ground Based Detectors to Solar Neutrons -- Statistical Investigations of Solar Neutron Events on the Basis of Ground Observations -- Observations of Solar Neutron Events by Ground Based Detectors, and Their Interpretation -- The Solar Neutron Decay Phenomenon -- Gamma Rays from Solar Energetic Particle Interactions with the Sun$1 (Bs Atmosphere -- Positron Generation in the Nuclear Interactions of Flare Energetic Particles in the Solar Atmosphere -- The Development of Models and Simulations for Solar Neutron and Gamma Ray Events.s
Keywords: Physics; Physical geography; Astrophysics; Nuclear physics; Physics; Extraterrestrial Physics, Space Sciences; Astrophysics and Astroparticles; Nuclear Physics, Heavy Ions, Hadrons; Geophysics/Geodesy.